2014
DOI: 10.1039/c4em00268g
|View full text |Cite
|
Sign up to set email alerts
|

Neurological abnormalities in a mercury exposed population among indigenous Wayana in Southeast Suriname

Abstract: The indigenous Wayana community of Puleowime (Apetina) in Suriname is susceptible to the effects of mercury because they consume large amounts of fish compared to mainstream communities. Small-scale and artisanal gold mining activities occur at numerous sites in eastern and southeastern Suriname placing the Wayana at risk from exposure to mercury released into the environment. A previous community-led risk assessment study showed that the Wayana were at a high lifetime risk of adverse effects from exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Significant literature exists on the neurotoxicity of MeHg upon the direct exposure of humans [35, 53] and animal models [12, 13, 54]. For instance, Weber et al .…”
Section: Discussionmentioning
confidence: 99%
“…Significant literature exists on the neurotoxicity of MeHg upon the direct exposure of humans [35, 53] and animal models [12, 13, 54]. For instance, Weber et al .…”
Section: Discussionmentioning
confidence: 99%
“…Limited surveillance of mercury contamination in Madre de Dios has suggested that the communities living near small‐scale gold mining operations may be at risk of health impacts from mercury exposures (Ashe, 2012; Diringer et al, 2015; Wyatt et al, 2017; Yard et al, 2012). Indeed, a number of studies of riverine communities in the Brazilian Amazon suggest mercury exposures in the region may be of a sufficient magnitude to cause subtle neurologic, motor, and somoatosensory deficits in adults (Dolbec et al, 2000; Lebel et al, 1996, 1998; Peplow & Augustine, 2014; Yokoo et al, 2003) and neurodevelopmental delays in infants (Dórea et al, 2012; Marques et al, 2016). However, for school‐aged children, little study has yet determined whether the levels detected in this region are leading to neurodevelopmental harm.…”
Section: Introductionmentioning
confidence: 99%
“…The indicators used to show that there is a problem worth consideration were (1) 58% of previously analyzed hair samples showed the Indigenous communities in question had mercury levels above the World Health Organization safety limit (10 ppm), and (2) case studies based on a battery of neurological tests in conjunction with hair mercury data found clinical evidence of mercury poisoning among Indigenous Wayana people living in the transborder region between Suriname and French Guiana [10].…”
Section: Indicatorsmentioning
confidence: 99%
“…Mercury exposure was found at levels causing adverse neurological effects among people in the Guiana region who are highly dependent on fish in their diet [8,9]. Health assessment studies showed victims are likely to have their physical and cognitive abilities damaged irreversibly [10]. There are reports that suicide and attempted suicide among the Indigenous populations of the upper Maroni occurred at a rate 13 times higher than the regional average [11].…”
Section: Introductionmentioning
confidence: 99%